Vivências de pacientes com câncer em cuidados paliativos e o significado da espiritualidade - Benites, Andréa Carolina [UNESP] (2014)
Although medicine reaches constant advancements in patient care with cancer, with the realization of early diagnosis and different treatment alternatives, there are cases where the cure or control are not possible and the disease progresses, making patient to pass through the so-called palliative care. Different studies have pointed out the importance of spirituality in quality of life, specially to coping with the disease and the possibility of death, both to patients and families. The maintenance of hope, new meaning of existence in face of the disease and reflections about the meaning of life are associated to spirituality. This study aimed to understand the meaning of spirituality before the pain of the disease and the possibility of death for cancer patients in palliative care. The subjects in the study were 5 male and 5 female adults/elderly, aged 44-71 years old, diagnosed with advanced cancer, patients of the Cancer Hospital of Barretos, the Palliative / Pain Care Unit. Was used a phenomenological method for collection and analysis of the participants' reports, which were obtained in individual interviews, which were based on the guiding question: how was your journey from diagnosis to the present moment, and as it is for you to experience this moment of your life in relation to feelings, fears and future expectations?. Four themes were unfolded: faith as hope of healing; support, trust and search for meaning / redefinition of life; religious practice as a support; the meaning of care offered by the health team, family and the holiness; the search for meaning in death and beliefs about the afterlife and the experience of transcendence. The worsening of the disease process and the experience of terminality mobilized various coping resources and reflections on the meaning of life and death. Among the various issues raised, it was observed that despite the pain and mental suffering, the spiritual dimension facilitated the search...